TRADISI BAHTSUL MASAIL DI PONDOK PESANTREN - Sayono, Joko (Jurnal Sejarah dan Budaya, 2009)
Abstract: Bahtsul masail is a scientific forum conducted by santri and Kyai to discuss vary of society problems, including religious, economical, political and social problems. The interesting phenomenon of this forum is the existence of yellow book (kitab kuning) as main reference in every decision making. The reuslts of Bahstul matsail are heterogen and dinamics that means many problems can be given its way out based on their reason and reference book. The main basic of thinking in decision making is goodness for people without neglecting rules of religious standard. It is viewed as moral obligation of Kyai and Santri thorought Pesantren as religious tradisional institution to mantain society situation and condition in order to approriate with religious norms.